PELAKSANAAN SUPERVISI AKADEMIK OLEH KEPALA SEKOLAH MADRASAH ALIYAH RAUDLATUL FIRDAUS KABUPATEN KUBU RAYA - Abdul Pandi (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This research is to find out: Implementation of Academic Supervision by the Principal of senior High School Raudlatul Firdaus, Kubu Raya Regency. The method used in this study is a descriptive method with a qualitative approach. The main data sources in this study were principals and teachers obtained through interviews, observations, and documentation. There are several research results that show that, the principal in planning academic supervision carries out several stages including the principal making a schedule and preparing instruments for the implementation of academic supervision to teachers, academic supervision is carried out in several steps such as the principal conducting class visits, class observations, involving teachers in meetings discussing the learning process, conducting problem solving discussions with teachers, improving teachers' academic abilities by holding wordshops and providing consultation time for teachers who have problems related to learning. And the principal is following up on the implementation of academic supervision that has been carried out so that it is not only the implementation of supervision, so that it has a beneficial effect on teachers at school, the principal is also required to make reports related to the results of the implementation of academic supervision to be published to all teachers who have been supervised so that the teacher can follow up on the results of supervision. so it can be concluded that the principal of senior High School Raudlatul Firdaus in terms of implementing academic supervision of teachers has gone through these stages so that after the implementation of supervision it brings changes to the learning process at school and easily achieves school goals that have been determined together.